Hormonal mechanisms regulating follicular wave dynamics: insights from the subordinate follicles during diameter deviation - Gomez León, Victor Enrique (2018)
Follicle diameter deviation has been identified as the pivotal morphological manifestation of follicle selection. Complexities in diameter deviation (F1 ~ 8.5 mm) have been reported based on the diameter of the largest subordinate follicle (F2) at time of follicle deviation (conventional F2 ≥ 7 or undersized < 7 mm). However, many of the hormonal mechanisms leading to this key event and regulating variation between individual follicular waves remain undefined. Our main objective was to characterize and categorized the variations during the follicular diameter deviation. Thus, based on the subordinate follicles point of view, a biological model for future follicle selection studies could be proposed. Paper 1 compared circulating FSH, LH, and P4 with the follicular dynamics during wave 1 vs 2, spontaneous vs induced wave 2, and conventional vs undersized deviations. Values were normalized to the day of expected diameter deviation (day 0) and compared using SAS PROC MIXED. The effect of different hormonal conditions on follicle dynamics was observed for F2 and not for F1. Increased frequency of undersized deviation was associated with high P4 and FSH but lower LH concentration. Although, the causes for conventional and undersized remains unclear. Paper 2 directly evaluated the role of P4 in the diameter deviation complexities by manipulating P4 (Experiment 1). Experiment 2 tested whether decreased LH was the mechanism whereby elevated P4 increases undersized deviations. Data were normalized to F1 ≥ 7.5mm (day 0) and compared using SAS PROC MIXED. Elevated P4 was linked to undersized deviation but this occurred either in increased or decreased LH activity and, surprisingly, increased or decreased circulating FSH. Paper 3 evaluated whether deficient LH activity was the underlying mechanism causing inhibition of follicular deviation and follicle growth only until 8.5mm in GnRH-antagonist (Acyline) treated heifers. Holstein heifers (n=24) were randomized: Control (n=8; Saline treatments), Acyline (n=8; 5μg/kg Acyline), or Acyline+hCG (n= 8; 5μg/kg Acyline plus hCG; 50 IU of hCG at start then 100 IU every 12h). Data were normalized to F1 ⁓ 7.5mm (day 0) and compared using SAS PROC MIXED. Dominant follicle selection and growth after deviation was inhibit by Acyline treatment and associated with ablation of LH pulses. However, restoration of this process happened after replacement of LH action by hCG treatment. Future molecular studies are in need to determinate the cause of the differences observed in the follicular deviation of waves during high and low progesterone.